Advances and Challenges for Nutrient Management in China in the 21st Century. Issue 4 (1st July 2013) - Sims, J. T.; Ma, L.; Oenema, O.; Dou, Z.; Zhang, F. S.
Abstract : Managing agricultural nutrients to provide a safe and secure food supply while protecting the environment remains one of the great challenges for the 21st century. The fourth International Nutrient Management Symposium (INMS), held in 2011 at the University of Delaware, addressed these issues via presentations, panel sessions, and field tours focused on latest technologies and policies available to increase nutrient use efficiency. Participants from the United States, Europe, Canada, and China discussed global trends and challenges, balancing food security and the environment in countries with struggling and emerging economics, nutrient management and transport at the catchment scale, new technologies for managing fertilizer and manure nutrients, and adaptive nutrient management practices for farm to watershed scales. A particular area of interest at the fourth INMS was nutrient management progress and challenges in China over the past 40 years. China's food security challenges and rapidly growing economy have led to major advances in agricultural production systems but also created severe nutrient pollution problems. This special collection of papers from the fourth INMS gives an overview of the remarkable progress China has made in nutrient management and highlights major challenges and changes in agri‐environmental policies and practices needed today. Lessons learned in China are of value to both developing and developed countries facing the common task of providing adequate food for an expanding world population, while protecting air and water quality and restoring damaged ecosystems.